A new species of genus Schizopelex McLachlan (Trichoptera, Sericostomatidae), from the southern Iberian Peninsula - Ruiz-García, Antonio; Ferreras-Romero, Manuel (Zootaxa, 2014)
The West Palearctic genus Schizopelex McLachlan 1876 is represented by eleven recognized species. The center of its distribution area is in Turkey, where seven species have been reported (Malicky 2004; Sipahiler 2005, 2012; Oláh 2010; Sipahiler & Pauls 2012). These 7 species are S. anatolica Schmid 1964, S. rhamnes Malicky 1976, S. sinopica Sipahiler 2012, S. yenicensis Sipahiler & Pauls 2012, S. boluensis Sipahiler 2012 (in Sipahiler & Pauls 2012), S. cachetica Martynov 1913a, S. pontica Martynov 1913b. Schizopelex cachetica and S. pontica have also been reported from the Caucasus and the Transcaucasia, respectively (Martynov 1913a, 1913b; Ivanov 2011). In addition, two species (S. huettingeri Malicky 1974 and S. persica Schmid 1964) are known from the Balkans and Iran, respectively. The two remaining species are distributed in the southwestern West Palearctic region (southwestern Europe): Schizopelex furcifera McLachlan 1880 has been reported from the northeastern Iberian Peninsula and the Pyrenees (González et al. 1992; Martínez-Menéndez & González 2010); Schizopelex festiva (Rambur 1842) is distributed throughout most of the Iberian Peninsula and the Maghreb (González et al. 1992; González & Martínez 2011).